Covariability and interaction of North Atlantic sea surface temperature and North Atlantic Oscillation in ECHAM3 greenhouse-gas scenario simulations - Heiko Paeth; Petra Friederichs; Andreas Hense (Meteorologische Zeitschrift, 2001)
The ocean-atmosphere interactions of sea surface temperature and the North Atlantic Oscillation as an atmospheric phenomenon are examined in an ensemble of climate change simulations. The principal task concentrates on the common climate change signals, the lead-lag relationship, the time-space covariability, and the aspect of predictability. The study is based on Monte Carlo experiments of the German coupled climate model ECHAM-3/LSG with increasing greenhouse-gas concentrations according to IPCC scenario A. The Atlantic SST variability is mainly determined by the greenhouse-gas induced warming signal with maximum temperature rise in the low latitudes whereas in the Icelandic region the CO2 influence is blotted out by intense natural variability. On a monthly time scale, the North Atlantic SST field is regionally affected by the NAO. An oceanic impact cannot be observed on this short time scale. The main oceanic response occurs in the Sargasso Sea, the Irminger Sea, and less pronounced in the subtropical North Atlantic building a tripole structure. A climatological index is defined indicating the main response of North Atlantic SST to the atmospheric forcing. This index is largely coherent with the index of the North Atlantic Oscillation on the interannual and decadal time scale. The covariability of sea surface temperature and sea level pressure in the North Atlantic sector amounts to 26 % of total variance. Die vorliegende Studie untersucht die Wechselwirkungen zwischen den MeeresoberflÄchentemperaturen (SST) im Nordatlantik und dem atmosphÄrischen PhÄnomen der Nordatlantik-Oszillation (NAO). Die Datengrundlage bildet ein Ensemble von vier Simulationen des gekoppelten Klimamodelles ECHAM-3/LSG mit externem Treibhausgasantrieb gemÄß IPCC-Szenario A. Neben dem Aspekt des gemeinsamen Klimasignales werden die Richtung der Einflussnahme im ozeanisch-atmosphÄrischen System, die raumzeitlichen AusprÄgungen der KovariabilitÄt und die Möglichkeiten zur Vorhersage betrachtet. Die SST-VariabilitÄt im Atlantik ist nach 1970 eindeutig von einem CO2-induzierten ErwÄrmungssignal geprÄgt. Dieses Signal tritt zuerst in den niederen Breiten auf und propagiert von dort aus polwÄrts, ist hingegen in den Regionen hÄufiger ZyklonenaktivitÄt nicht nachweisbar. Auf der Monatszeitskala beeinflusst die NAO die VariabilitÄt des nordatlantischen SST-Feldes, wohingegen eine andersgerichtete Einflußnahme nicht zu verzeichnen ist. Die Zentren des Kreuzkorrelationsmusters liegen in der Sargasso-See und der Irminger-See sowie in schwÄcherer AusprÄgung im östlichen subtropischen Atlantik, so dass ein dreipoliges Muster vorliegt. Aus diesem Muster wird ein Indexwert definiert, welcher die wesentliche ozeanische Reaktion auf den atmosphÄrischen Antrieb beschreibt. Dieser Index ist auf der interannuellen bis dekadischen Zeitskala weitgehend kohÄrent mit dem Index der NAO. Die raumzeitliche KovariabilitÄt von nordatlantischem SSTund Bodendruckfeld belÄuft sich im Modell auf 26 % der Gesamtvarianz.